Coronary Artery Abnormalities as the Cause of Sudden Cardiac Death: A 20-Year Review. (June 2018) - Pawlowicz, Bernard; Fernandes, John; Nair, Vidhya
Abstract : Abstract: In this case series, we delve into the database of medicolegal cases of the Forensic Pathology Department at Hamilton Health Sciences in Hamilton Ontario from the last 20 years (1996–2017), and review cases of sudden cardiac death due to coronary artery abnormalities. We found 17 cases that fit the criteria, which gave us an incidence of 1.34 per 1000 cases. These cases were further audited for age, sex, type of coronary artery abnormality, symptoms before demise, circumstances of death, presence of significant atherosclerotic disease, and toxicology. Two more recent cases underwent postmortem genetic testing, and we reported on the result of one of these molecular studies. In our case series, the most commonly affected coronary artery was the right coronary artery, with the most common anomaly being abnormal origin from the left sinus of Valsalva. Although the literature maintains that left coronary artery from the opposite sinus is associated with higher incidence of SCD, our study shows that RCAs from the opposite aortic sinus, including those deemed to be low risk by classification, can be causes of SCD.